Identification and Characterization of oriT and Two Mobilization Genes Required for Conjugative Transfer of Salmonella Genomic Island 1 - Kiss, János; Szabó, Mónika; Hegyi, Anna; Douard, Gregory; Praud, Karine; Nagy, István; Olasz, Ferenc; Cloeckaert, Axel; Doublet, Benoît (Frontiers in Microbiology, 2019)
The SGI1-family integrative mobilizable elements considerably contribute to the spread of resistance to critically important antibiotics among enteric bacteria. Even though that many aspects of SGI1 mobilization by IncA/C plasmids have been explored, the basic transfer functions such as oriT and self-encoded mobilization proteins remain undiscovered. Here we describe the mobilization region of SGI1 that is well conserved throughout the family and carries the oriTSGI1 and two genes that are essential for the conjugative transfer of SGI1. OriTSGI1 is located in the vicinity of the two mobilization genes and proved to be a 125 bp GC-rich sequence with several important inverted repeat motifs. The two mobilization genes mpsA and mpsB (originally annotated as S020 and S019, respectively) encode proteins that, unlike the helper plasmid-encoded relaxase, are necessary for SGI1 transfer. They are expressed from a bicistronic mRNA, but MpsB can also be produced from its own mRNA. The structure predictions suggest that MpsA belongs to the lambda tyrosine recombinase family, while MpsB resembles the N-terminal core DNA binding domains of these enzymes. The results suggest that MpsA may act as an atypical relaxase, which needs MpsB for SGI1 transfer. However, the helper plasmid-encoded relaxase is required to achieve the high transfer rate observed with the WT IncA/C-SGI1 system.